2022
DOI: 10.4103/ua.ua_113_21
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about prostate cancer and its screening in Medina, Jeddah, and Makkah, Saudi Arabia population

Abstract: Background: Prostate cancer (PCa) is a global burden on public health; it has been ranked as the second common cancer worldwide, with 1.3 million new cases in 2018. Developed countries have a higher incidence than in developing countries. Because of the lack of studies on PCa in Saudi Arabia, our study aims to measure the awareness about PCa and knowledge of PCa screening practices among men in Medina, Jeddah, and Makkah, Saudi Arabia. Methodology: A cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…This is because this was lower than what previous studies conducted in South Africa and Kenya. 11,19 However, poor recognition of being of Black race as a risk factor to PCa in the present study was consistent with a study conducted in Nigeria. 20 These similarities may occur since the two studies were conducted in African regions which indicates that the men in this region are not aware of race as a risk factor to PCa.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is because this was lower than what previous studies conducted in South Africa and Kenya. 11,19 However, poor recognition of being of Black race as a risk factor to PCa in the present study was consistent with a study conducted in Nigeria. 20 These similarities may occur since the two studies were conducted in African regions which indicates that the men in this region are not aware of race as a risk factor to PCa.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies conducted in Malaysia and South Africa found out that men have poor knowledge on PCa. 19,29 . The present study contradicts their findings since participants in this study showed high levels of levels of PCa in general.…”
Section: Discussionmentioning
confidence: 99%
“…This vast disparity in metastasis rates between countries may be caused by a lack of population awareness of PCa symptoms and screening. A 2022 cross-sectional study in the western area of Saudi Arabia identified that 47.5% of participants had poor knowledge regarding PCa risk factors, symptoms, and screening 14 . Generally, cancer screening uptake is low among the Saudi population 15 .…”
Section: Discussionmentioning
confidence: 99%
“…6,14,19,20 Bir çalışmada ise ailesinde prostat kanseri tanısı almış olan kişilerin yalnızca %15.9'unun prostat kanseri taramalarına ilişkin bilgi düzeyinin iyi olduğu saptanmıştır. 21 Prostat kanseri risk faktörleri arasında ailesel yatkınlık yer almaktadır. Ailesel yatkınlığın kanser gelişiminde ve kansere bağlı ölümlerde etkili olması nedeniyle, aile ya da akrabalarında prostat kanseri tanısı alan hemşirelik öğrencilerinin tarama yöntemlerini daha fazla araştırdıkları ve dolayısıyla daha fazla bilgiye sahip olduğu düşünülmektedir.…”
Section: Hemşirelikunclassified